2015
DOI: 10.1111/bjh.13867
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of diffuse large B‐cell lymphoma with secondary central nervous system involvement: encouraging efficacy using CNS‐penetrating R‐IDARAM chemotherapy

Abstract: Diffuse large B-cell lymphoma with secondary involvement of the central nervous system (SCNS-DLBCL) is a rare condition carrying a poor prognosis. No optimal therapeutic regimen has been identified. We retrospectively analysed 23 patients with SCNS-DLBCL treated with R-IDARAM (rituximab 375 mg/m(2) IV day 1; methotrexate 12·5 mg by intrathecal injection day 1; idarubicin 10 mg/m(2) /day IV days 1 and 2; dexamethasone 100 mg/day IV infusion over 12 h days 1-3; cytosine arabinoside 1000 mg/m(2) /day IV over 1 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Transplantation was not planned for all patients, and only 5 patients received a transplant. The authors conclude that this regimen has an encouraging outcome in newly diagnosed SCNSL …”
Section: Discussionmentioning
confidence: 82%
“…Transplantation was not planned for all patients, and only 5 patients received a transplant. The authors conclude that this regimen has an encouraging outcome in newly diagnosed SCNSL …”
Section: Discussionmentioning
confidence: 82%
“…In a second study with HD-MTX, rituximab, cytarabine and idarubicin (R-IDARAM) 4 out of 10 (40%) patients achieved a CR. Median OS of both studies was 25.1 months and more than 30 months, respectively [14,18]. In a pilot study with dose-adjusted EPOCH (etoposide, cyclophosphamide, doxorubicin, vincristine, prednisone) plus rituximab 8 out of 8 patients achieved a CR [15].…”
Section: Discussionmentioning
confidence: 95%
“…No further study was reported about the efficacy and safety of R-IDARAM on PCNSL patients with overall survival and progression free survival. In 2016, Maciocia P et al treated diffuse large B-cell lymphoma with secondary CNSL involvement which also showed encouraging efficacy and well tolerance [ 13 ]. This study evaluated the efficacy and safety of R-IDARAM chemotherapy and intrathecal immunochemotherapy in patients with PCNSL.…”
Section: Discussionmentioning
confidence: 99%